Problematika Pembelajaran Jarak Jauh - Alifatun Nasirah; Jauharotul Makniyah (Fakta: Jurnal Pendidikan Agama Islam, 2022)
The spread of the Corona (Covid-19)has several impacts on the continuity of education. With all levels of readiness for education in Indonesia, it must follow the prescribed flow and help with emergencies in schools. The change that is felt is the learning system, in the form of distance learning. Meanwhile, some parents do not understand what social media or the internet is.The purpose of this study was to determine the problems faced by the guardians of the students, to describe the impact of the problems faced by the parents, and to find out how the parents were dealing with distance learning problems at MI Nurul Huda Pakandangan Barat Sumenep.This research design used a qualitative descriptive study, using the phenomenological study method. The data source of this research is in the form of student guardians. Obtaining data used are interviews and documentation that shows about the subject. The results showed that the problems faced by students' guardians in distance learning at MI Nurul Huda Pakandangan Barat are wasteful use of quotas or pulses, interference with signals or internet networks, limited ability of guardians in understanding lessons, disruption of child development, and poor children's character. , the impact of the problems of student guardians in distance learning at MI Nurul Huda is the compulsion of guardians who live in the majority of farmers and fishermen to use technology, reduced working time, and the ability of student guardians to understand learning material, the way student guardians deal with distance learning problems in MI Nurul Huda is trying to keep children carrying out the same daily routine when studying at school, become friends to learn, build smooth communication between parents and teachers, and assist children in distance learning